Benzo[d]imidazole and Aliphatic α-Amino Acid Derived Primary Amines in Asymmetric Aldol Reactions - Mohite, Pravinkumar Hansraj; Drabina, Pavel; Bureš, Filip (Synlett, 2014)
Starting from essential α-amino acids, four new benzo[d]imidazole and alkyl-chain-substituted primary amines were synthesized. The reaction sequence involves activation of the Boc-amino acid carboxylic acid, reaction with o-phenylenediamine, and subsequent cyclization to benzo[d]imidazole. N-Methylation and final Boc group removal afforded four new primary amines. The synthesized amines were preliminarily applied as organocatalysts in an asymmetric version of the aldol reaction between 4-nitrobenzaldehyde and acetone/cyclohexanone, achieving chemical yields of 40–64% and ee and de values up to 65 and 96%, respectively.
Keywords: benzo[d]imidazole; primary amine; α-amino acid; asymmetric aldol reaction; organocatalysis